The Assembly and Installation of Solar Powered Public Street Lights (PJU) at Panti Asuhan Putri Aisyiah Dau Malang - Gumono; Sugeng Hadi Susilo; Agus Setiawan; Asrori (Yayasan Payungi Smart Madani, 2021)
The paper discusses the problem of increasing security for residents in panti asuhan putri aisiyah dau malang area, Jl. Engineer Soekarno II no. 4 RT 01 RW 01 Dadaprejo Village, Junrejo District, Malang Regency. One of the most important is lighting. The installation of public street lighting is still minimal, so it is far from meeting security and safety standards. In order to ensure the availability of safe and reliable street lighting, training on the assembly of solar-powered street lighting (PJU) was conducted at panti asuhan putri aisiyah dau malang, Jl. Engineer Soekarno II no. 4 RT 01 RW 01 Dadaprejo Village, Junrejo District, Malang Regency. Prior to the assembly process for street lighting, a brief training was conducted on the assembly of solar-powered PJU lampposts and their installation, for residents at panti asuhan putri aisiyah dau malang Jl. Engineer Soekarno II no. 4 RT 01 RW 01 Dadaprejo Village, Junrejo District, Malang Regency., so that he has skills that can be developed. The result of the PKM is an increase in the knowledge and skills of the residents of the panti asuhan putri aisiyah dau malang in the field of fabrication and installation of solar-powered PJU lights. In addition, the installation of 3 Solar Powered PJU lights that are safe and reliable, and have an impact on increasing environmental security and residents' activities at night in the panti asuhan putri aisiyah dau malang. Keywords: Public Street Lighting, Solar Cell Lamps, Lamp Posts